Am I _____ enough? - Amelia Yuliana Jamil (Nanyang Technological University, 2020)
“Am I ____ enough” explores the hidden struggle behind faith, particularly being a Muslimah – a female Muslim. It is a moving image that seeks to confront the never-ending judgment from society whether one is truly Muslim enough from her clothing and her actions. As the artists explores the different environment that challenges this predicament, she holds a conversation between herself and God. We tend to forget that everyone has their own spiritual journey. This project hopes to allow the Muslim community to understand that change, or struggle isn’t necessarily bad, but in fact essential in being a more open and accepting community.